Management and gender in higher education - O'Connor, Pat, 1950- (Book collections on Project MUSE., 2014)
O'Connor provides a definitive examination of Irish higher education: exploring its nature and purpose, and locating it in the context of the state and the market. She presents new research on an elite group: senior managers in universities. They are relatively powerful in relation to their students and staff but relatively powerless in relation to wider neo-liberal forces. Drawing on policy analysis and interviews with those at the top 3 levels of university management, the book provides an in-depth analysis of the structures, cultures and practices at that level and locates these in a cross national context.